2022
DOI: 10.1155/2022/4656661
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LTF as a Prognostic Biomarker for Osteosarcoma

Abstract: Osteosarcoma remains a major health problem in teenagers. However, its pathogenesis mechanism remains not fully elucidated. This study aims to identify the prognostic biomarkers for osteosarcoma. In this study, we selected genes with a median absolute deviation (MAD) value of the top 5000 in the GSE32981 dataset for subsequent analysis. Weighted correlation network analysis (WGCNA) was used to construct a coexpression network. WGCNA showed that the tan module and midnight blue module were highly correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…LTF is widely considered a tumor suppressor. Consistent with the results of this study, patients with OS with low LTF levels showed lower survival rates, which may be attributed to the inhibitory effect of LTF on tumor cell proliferation (31). BNIP3, CDKN2A, PHLDA2, and UCHL1 are genes that we found highly expressed in OS samples.…”
Section: Discussionsupporting
confidence: 90%
“…LTF is widely considered a tumor suppressor. Consistent with the results of this study, patients with OS with low LTF levels showed lower survival rates, which may be attributed to the inhibitory effect of LTF on tumor cell proliferation (31). BNIP3, CDKN2A, PHLDA2, and UCHL1 are genes that we found highly expressed in OS samples.…”
Section: Discussionsupporting
confidence: 90%
“…A lower expression of LTF has been shown in tumours such as prostate cancer (CaP), NPC, osteosarcoma, clear cell renal cell carcinoma (ccRCC) and OSCC [ 21 , 22 , 23 , 24 , 25 , 26 ]. Shaheduzzaman et al [ 21 ] demonstrated that LTF mRNA expression in tumour cells revealed a marked downregulation of LTF , with significant associations with a decreased prostate-specific antigen (PSA) recurrence-free survival of patients with CaP.…”
Section: Discussionmentioning
confidence: 99%
“…It not only possesses iron binding/transferring but also demonstrates antibacterial, antiviral, and anti-inflammatory. Recently, an increased focus has been on elucidating the LTF in cancer, researchers have reported that LTF gene behaves like a tumor suppressor gene in diverse tumors, such as renal cancer, prostate cancer and gastric cancer et al (Ni et al 2020;Gołąbek et al 2022;Zhao et al 2021;Luo et al 2015;Yi et al 2006;Liu et al 2022). They found that the absent expression or downregulation of LTF is widespread in these tumors and promotes tumor proliferation, while the overexpression of LTF inhibits the proliferation.…”
Section: Introductionmentioning
confidence: 99%